Shipwrecks, storms and tears: the dysphoric vision of faith in Catherine de Saint-Augustin - Pontelli, Alessandro (Oltreoceano - Rivista sulle migrazioni, 2024)
This article aims to investigate the use of the ‘aquatic metaphor’ within what is considered to be the first Vie written in New France. La Vie de la mère Catherine de Saint-Augustin was in fact published by Father Paul Ragueneau, the nun’s spiritual director, in 1671 following her death. Although it is an autobiographical writing at its infancy, the work undoubtedly presents some interesting features from a narrative and linguistic point of view. Through the study carried out by Gaston Bachelard in his essay L’eau et les rêves (1942), an attempt will be made to emphasise and give meaning to the woman’s all-round use of the water element. In particular, the latter is exploited by the nun to express her inner state. After her arrival on the new continent on 19 August 1648, the hospitalière’s writings are strongly influenced by the Atlantic crossing during which her existence seems to oscillate between life and death. In fact, the ship and the storm are at the centre of numerous metaphors used to describe difficult conditions or moments in which Catherine finds herself suspended between two contrasting situations. As a highly symbolic element in the Christian liturgy, holy water is also one of the symbols adopted by the nun as an instrument of purification from evil and on which she relies in times of need. Thus, it becomes the means by which God is able to protect the faithful from the demonic visions that torment her. We will then see how, even in Hell, water acquires a highly symbolic meaning as the perfect expression of the union of opposites. Finally, we will give space to tears and weeping. The latter is the main element through which the young woman expresses her sorrow, but, depending on the circumstances, it is also a medium to invoke divine intercession. Therefore, water becomes a powerful symbol that is linked to its surroundings, allowing those who use it to build their own image but also to come into closer contact with the spiritual entity.